Assessment of Preoperative Anxiety Among Surgical Patients - Sinmiloluwa Eyitayo Maiye; Ümran Dal Yılmaz (Mediterranean Nursing and Midwifery, 2022)

(untitled)
Objective:This study aims to assess preoperative anxiety among surgical patients.Method:This descriptive cross-sectional study was conducted at the Dr. Suat Gunsel University of Kyrenia Hospital and Near East University Hospital from October 2020 toJanuary 2021. A total of 81 patients voluntarily participated in this study. Data were collected by Personal Information Form and Amsterdam Preoperative Anxiety and Information Scale. Descriptive statistics, Student’s t-test, Mann–Whitney U Test, Kruskal–Wallis test, and post hoc test were used to compare the data, while Pearson’s correlation was used to evaluate the correlation between the continuous variables.Results:The average Amsterdam Preoperative Anxiety and Information Scale anxiety level was found to be 10.6 ± 6.5, the average scores of Amsterdam Preoperative Anxiety and Information Scale sub-dimensions were 4.9 ± 2.5 for anesthesia-related anxiety, 5.6 ± 2.4 for anxiety about the surgery, and 6.1 ± 2.4 for the information desire. The result of the study showed that there was a statistically significanct relationship between gender and the patient’s level of preoperative anxiety among preoperative surgical patients.Conclusion:Based on the results of the study, it may be recommended to assess the patient’s anxiety and provide appropriate and necessary information.